Myosin heavy chain as biomarker in the prevention of sarcopenia - Desy Nofita Sari; Roman Ardian Goenarjo; Chin Leong Lim; Imelda Rosalyn Sianipar (Faculty of Medicine, Universitas Trisakti, 2026)
Sarcopenia, or the age-related loss of skeletal muscle mass and function, can reduce total muscle contractile capacity and increase the likelihood of physical disability in older adults. The loss of muscle mass and contractile performance is generally thought to be multifactorial, with as possible contributing factor an age-related shift in the expressed amounts of myosin heavy chain (MyHC) isoforms. The composition of adult human skeletal muscle consists of a mixture of three distinct MyHC isoforms (I, IIA, and IIX). This literature review aimed to explore studies focused on the signs of sarcopenia, the early detection of initial symptoms, and awareness among the aging population. We aimed to understand the molecular changes in muscle fibers as people age and to help inform the early intervention approach to prevent sarcopenia. The literature search was conducted in several databases between 2020 to 2025, including PubMed, ScienceDirect, and SpringerLink. The search terms consisted of “sarcopenia”, “muscle mass”, “early detection”, and “myosin heavy chain”. Inclusion criteria included original full-text English-language studies on the cellular and molecular physiology of sarcopenia. Molecular changes in myosin heavy chain vary across different age groups, suggesting the potential for early detection of muscle aging. The review is limited by the variability in the definition and measurement of sarcopenia across different studies, which may affect the generalizability of the findings. This review highlights the potential significance of identification and sarcopenia management in elderly individuals. The findings would be helpful for clinicians, researchers, and policymakers to improve elderly care and quality of life.